A Study of Perceptions of Investors Regarding Choice of Assets Allocations and Portfolio Management with Respect to Major Cities of Gujarat - Singh Rathod, Harishchandra; Chauhan, Rahul; Tria Putri, Librina; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
In the contemporary trend investment in various securities is a big question for the investors because of various alternatives are available for the investment in which we can comprise national and international. An objective of this paper is to study the perception of the investors concerning the choice of the asset allocation and portfolio management in the major cities of the Gujarat. For the investment, portfolio management and selection of securities in portfolio is important. In the era of globalization, portfolio management plays an important role in investing in securities. Portfolio management is both art and science. It is much more than the application of a formula on a set of financial information inputs provided by the Financial Advisor to the selection of securities from the catalog or the security analyst. Intention of this paper is to find out the perceptions of the new investment options of assets allocation and the portfolio management in the major cities of the Gujarat and perceptions for selection of the securities because of in Gujarat the cognizance of the investment alternatives is less in compared to other states. For this analytical study primary data is useful source of information, so questionnaire and interview are the best tools for the research. For analysis of the data Fisher’s exact test is used and based on that conclusion of this paper is drawn and the main problem faced by the investors may derive.